2012
DOI: 10.1007/s10456-012-9322-9
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease 4 protects neuron degeneration by promoting angiogenesis, neurogenesis, and neuronal survival under stress

Abstract: Altered RNA processing is an underlying mechanism of amyotrophic lateral sclerosis (ALS). Missense mutations in a number of genes involved in RNA function and metabolisms are associated with ALS. Among these genes is angiogenin (ANG), the fifth member of the vertebrate-specific, secreted ribonuclease superfamily. ANG is an angiogenic ribonuclease, and both its angiogenic and ribonucleolytic activities are important for motor neuron health. Ribonuclease 4 (RNASE4), the fourth member of this superfamily, shares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 64 publications
1
56
0
Order By: Relevance
“…However, the biological roles of RNASE4 are still largely unclear. Recent studies have shown that, similar to ANG, RNASE4 is able to protect against neuron degeneration through promotion of angiogenesis, neurogenesis, and neuronal survival under conditions of stress [33]. Our unpublished data indicated that RNASE4 possesses tumorigenic activity.…”
Section: Ang Gene Arrangementmentioning
confidence: 84%
“…However, the biological roles of RNASE4 are still largely unclear. Recent studies have shown that, similar to ANG, RNASE4 is able to protect against neuron degeneration through promotion of angiogenesis, neurogenesis, and neuronal survival under conditions of stress [33]. Our unpublished data indicated that RNASE4 possesses tumorigenic activity.…”
Section: Ang Gene Arrangementmentioning
confidence: 84%
“…The secreted RNase A4 is located at the same genetic locus as angiogenin, and both genes share the same promoters. Both of these factors are able to induce neurogenesis and neovascularization [17]. All these properties might exert a general impact on tissue formation and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA synthesis and reverse transcriptionpolymerase chain reaction Five micrograms of total RNA from cell cultures was reverse transcribed with the cDNA synthesis kit (MMLV-RT; Life Technologies) and with oligo-dT (12)(13)(14)(15)(16)(17)(18) -primer. For tendon and muscle tissue, the entire material was used for cDNA synthesis, which was carried out after DNase treatment to remove genomic DNA according to the protocol of the supplier (Revert Aid First Strand cDNA synthesis Kit; Fermentas) using random hexamer primers.…”
Section: Isolation Of Rnamentioning
confidence: 99%
“…Positively selected genes had a significantly higher ratio of nonsynonymous substitutions to synonymous substitutions than other genes in the high-altitude snub-nosed monkeys (P = 3.84 × 10 −3 for R. strykeri, 3.45 × 10 −6 for R. bieti, and 5.10 × 10 −8 for R. roxellana) (Supplementary Table 8). Further examination of these 16 genes found that 6 genes, including ARMC2, NT5DC1, RNASE4, CDT1, RTEL1, and DNAH11, have functional associations with lung function, angiogenesis, DNA repair, or respiratory cilia movement, suggesting a role in the high-altitude adaptation of the snub-nosed monkeys [19][20][21][22][23][24] (Table 1). Moreover, when the common substitutions for these six genes were examined in more mammalian species with publicly available genomes, no identical substitutions were found in those species (Supplementary Table 9 and Supplementary Note).…”
Section: Volume 48 | Number 8 | August 2016 Nature Genetics L E T T Ementioning
confidence: 99%
“…4c,d), suggesting that the p.Ala537Val substitution might contribute to the increased resistance to UV radiation of the high-altitude snubnosed monkeys. RNASE4 is a member of the RNase superfamily and has been reported to induce angiogenesis 19,26 . The coding regions of RNASE4 and its high-altitude variants were synthesized and Figure 3 Heat map of genes enriched for expression in the tissues of R. bieti and M. mulatta.…”
Section: Volume 48 | Number 8 | August 2016 Nature Genetics L E T T Ementioning
confidence: 99%